Sorção de fósforo em solos do semiárido - Vieira, Montesquieu da Silva (2017)
The Brazilian semi-arid soils have not yet been well studied in soil sorption processes and availability of phosphorus (P), in order to better understand the interaction of this nutrient with the soil. The objective of this work was to quantify the sorption of P and its kinetics in semi-arid soils and correlate their values with the related characteristics to the Soil Phosphorus Capacity Factor (PCF). Soil samples collected in the 0-30 cm depth layer of ten representative soils of the semi-arid region located between the Piranhas-Açu (RN) and Jaguaribe (CE) valleys were used. The used P concentrations of the equilibrium solutions to adjust the Langmuir and Freundlich isotherms were defined according to the remaining phosphorus (P-rem) values of the soils. For each soil, these isotherms were adjusted by non-linear regression technique and then, the related parameters to the sorption of P were estimated. The isotherms were adequate to quantify the sorption of P in the semi-arid soils. P was sorbed in higher amounts in the more clayey, alkaline and calcium rich soils, which shows greater importance of P precipitation with calcium in the P sorption process in these soils. In the studied soils, both the clay content and the P-rem content correlated well with the Maximum Phosphorus Sorption Capacity (MPSC) of the soils, but the P-rem was higher than the clay content in relation to the predictive capacity of the Phosphorus (PCF) of soils. To evaluate the kinetics of P sorption in soils, soil samples were contacted with 0.01 mol L-1 CaCl2 solutions containing the concentrations of 6 and 60 mg L-1 of P, and then stirred for nine equilibration times (5, 20, 40, 60, 120, 180, 600, 960 and 1440 minutes). At the end of each equilibration time, the obtained suspensions were filtered and the final concentration of P in the solution was analyzed. Phosphorus sorption kinetics were very large in the first moments of contact of phosphorus with soils, showed a dramatic decrease in the first five minutes of contact of phosphorus with these soils, and then tended to stabilize at a close value of zero along time. The amount of sorbed phosphorus in soil and the speed of this sorption was higher in soils with higher phosphate buffer capacity